Stockholm manuscript S 230 and its Prussian context - Leszczyńska, Agnieszka (Interdisciplinary Studies in Musicology, 2018)
The manuscript S 230, held in the National Library of Sweden in Stockholm, has not been thoroughly investigated until now. The only extant partbook of the source contains thirty two works, comprising motets and German songs. Only four of them bear the composers’ names: Orlande de Lassus, Franciscus de Rivulo, Johannes de Vienna and Joachim a Burck. Among the composers of anonymous works to have been identified are Jacob Bultel, Jacobus Clemens non Papa, Arnold Feys, Nicolas Gombert, Josquin des Prez and Jacob Meiland, as well as Lassus and Rivulo. At least two works are unique to this source: Rivulo’s A Domino egressa est res ista and Vienna’s Wohl dem, der den Herrenfiirchtet. The text of Rivulo’s motet is taken from the non-Vulgate version of the Book of Genesis, and the only other composer to write music to these words was Johannes Wanning, who succeeded Rivulo as magister chori musici at the Marian church in Gdańsk in 1569, five years after the latter’s death. Johannes de Vienna was composer at the Königsberg court in 1564-1568 and 1571 1576. The work from the Stockholm manuscript is his only extant composition. Two motets from the Swedish collection also appear in the Prussian manuscript J 40 24-28, held in the Copernican Library in Toruń: the anonymous Non est bonum and Rivulo’s Nuptiaefactae sunt.